Ride the Crepe Ring - Marlowe, Stephen, 1928-2008; Fuqua, Robert, 1905-1959 (Salt Lake City, UT : Project Gutenberg, 2021)
"Ride the Crepe Ring" by Milton Lesser is a science fiction novel written in the early 1950s. Set in a futuristic universe where space travel is commonplace, the story follows Socrates Smith, a resort operator on Mimas, one of Saturn's moons, as he seeks to attract tourists to his unique offering of rides through Saturn's rings. The book explores themes of adventure, safety, and personal relationships as Socrates navigates both his business aspirations and his connection with a spirited young woman named Norma. The plot centers around Socrates Smith and his attempt to make Mimas a popular tourist destination by offering thrilling rides through the bright rings of Saturn. Norma, an adventurous girl, is determined to join in on the excitement despite Socrates$1 (Bwarnings about the dangers associated with the darker crepe ring. The conflict escalates when Norma ventures into the crepe ring on her own, leading to a hazardous situation that requires Socrates to save her and a tourist named Mrs. Entwhistle. Through dynamic space adventures marked by dodging meteors and overcoming perilous conditions, the story highlights Socrates' growing affection for Norma and culminates in a romantic resolution that intertwines their fates amidst the backdrop of thrilling space exploration. (This is an automatically generated summary.)s
Release date is 2021-07-05
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Short stories; Space ships -- Fiction; Saturn (Planet) -- Fiction; Tourists -- Fiction; Mimas (Satellite) -- Fiction